Epidemiology of infective endocarditis before versus after change of international guidelines: a systematic review. (March 2021) - Williams, Michael L.; Doyle, Mathew P.; McNamara, Nicholas; Tardo, Daniel; Mathew, Manish; Robinson, Benjamin
Introduction: All major international guidelines for the management of infective endocarditis (IE) have undergone major revisions, recommending antibiotic prophylaxis (AP) restriction to high-risk patients or foregoing AP completely. We performed a systematic review to investigate the effect of these guideline changes on the global incidence of IE. Methods: Electronic database searches were performed using Ovid Medline, EMBASE and Web of Science. Studies were included if they compared the incidence of IE prior to and following any change in international guideline recommendations. Relevant studies fulfilling the predefined search criteria were categorized according to their inclusion of either adult or pediatric patients. Incidence of IE, causative microorganisms and AP prescription rates were compared following international guideline updates. Results: Sixteen studies were included, reporting over 1.3 million cases of IE. The crude incidence of IE following guideline updates has increased globally. Adjusted incidence increased in one study after European guideline updates, while North American rates did not increase. Cases of IE with a causative pathogen identified ranged from 62% to 91%. Rates of streptococcal IE varied across adult and pediatric populations, while the relative proportion of staphylococcal IE increased (range pre-guidelines 16–24.8%, range post-guidelines 26–43%). AP prescription trends were reduced in both moderate and high-risk patients following guideline updates. Discussion: The restriction of AP to only high-risk patients has not resulted in an increase in the incidence of streptococcal IE in North American populations. The evidence of the impact of AP restriction on IE incidence is still unclear for other populations. Future population-based studies with adjusted incidence of IE, AP prescription rates and accurate pathogen identification are required to delineate findings further in these other regions.